2018
DOI: 10.1186/s40104-018-0249-x
|View full text |Cite
|
Sign up to set email alerts
|

Does intra-ruminal nitrogen recycling waste valuable resources? A review of major players and their manipulation

Abstract: Nitrogenous emissions from ruminant livestock production are of increasing public concern and, together with methane, contribute to environmental pollution. The main cause of nitrogen-(N)-containing emissions is the inadequate provision of N to ruminants, leading to an excess of ammonia in the rumen, which is subsequently excreted. Depending on the size and molecular structure, various bacterial, protozoal and fungal species are involved in the ruminal breakdown of nitrogenous compounds (NC). Decelerating rumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 218 publications
1
43
1
3
Order By: Relevance
“…represented the majority of bacteria, consistent with earlier observations [40]. The higher abundance in the ruminal fluid from cows fed SI compared to FH could be related to better accessibility of feed protein, as Prevotella are known for proteolytic and peptidolytic activity [41]. B. fibrisolvens also displays proteolytic activity [41] and was elevated through feeding FH compared to SI, but its overall relative abundances were low.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…represented the majority of bacteria, consistent with earlier observations [40]. The higher abundance in the ruminal fluid from cows fed SI compared to FH could be related to better accessibility of feed protein, as Prevotella are known for proteolytic and peptidolytic activity [41]. B. fibrisolvens also displays proteolytic activity [41] and was elevated through feeding FH compared to SI, but its overall relative abundances were low.…”
Section: Discussionsupporting
confidence: 88%
“…The higher abundance in the ruminal fluid from cows fed SI compared to FH could be related to better accessibility of feed protein, as Prevotella are known for proteolytic and peptidolytic activity [41]. B. fibrisolvens also displays proteolytic activity [41] and was elevated through feeding FH compared to SI, but its overall relative abundances were low. Carbohydrate-degrading bacteria F. succinognenes, R. albus, and R. flavefaciens showed together a high relative abundance, presumably reflecting the forage-only diet.…”
Section: Discussionmentioning
confidence: 99%
“…This study was the first to demonstrate that not only were phages prevalent in the rumen, a finding subsequently confirmed using TEM (Hoogenraad et al, 1967), it also demonstrated that the phages found in the rumen differed from those present in other environments. This primary investigation was followed by numerous studies conducted in laboratories across the globe (Iverson and Millis, 1976a;Tyutikov et al, 1980;Hazlewood et al, 1983;Tamada et al, 1985;Nemcova et al, 1993;Styriak et al, 1994;Ambrozic et al, 2001). The majority of these studies were conducted in the 1980's and 1990's, with very few phage isolations reported in the literature beyond this era.…”
Section: Culture-based Viral Isolations and Genome Sequencingmentioning
confidence: 99%
“…The final stages of viral replication results in the accumulation of intact viral particles inside the cells and fragmentation (lysis) of the cell membrane, causing cell death and the release of progeny viral particles. Lysis also releases remnants of the microbial cell, including cell wall fragments as well as proteins and nucleic acids, which may then be taken up and utilized by other rumen microbes, a process often described as intra-ruminal recycling (Firkins et al, 1992;Hartinger et al, 2018) (Figure 2A). The recycling of nutrients amongst microbes was initially regarded as being a negative consequence of viral activity, limiting the amount of microbial protein carried through to the lower intestine where it can be absorbed by the animal (Leng and Nolan, 1984).…”
Section: Roles Of Viruses In the Rumenmentioning
confidence: 99%
“…The increase in nitrogen consumption is in line with the DMI presented by the animals fed increasing levels of maniçoba in the diets. The increase in faecal nitrogen may be related to the attempt to synchronize the availability of energy and protein for the rumen microorganisms, which may have increased the digestibility of the eliminated CPmainly through faeces (Hartinger et al, 2018). According to Getahun et al (2019), the N found in the faeces derives from the microbial cells formed in the large intestine, enzyme excretion and from food that has not been degraded in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%